2003
DOI: 10.3346/jkms.2003.18.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Pectus Excavatum

Abstract: The aim of this study was to compare clinical outcomes in pectus excavatum patients undergoing a Ravitch operation with those undergoing a Nuss procedure. Retrospective study was conducted on one hundred and twenty three patients who underwent Ravitch operation (n=16) and Nuss procedure (n=107) between 1995 and 2002. Mean age of the patients was 7.9+/-6.2 yr. In the Ravitch group, operation time was 196.9+/-61.0 min, and required 10.2+/-2.6 chondral bone resections. Average hospital stay time was 15.9 days. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Manual search of reference lists did not yield any new studies. After applying the selection criteria, 13 comparative studies (6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) were finally included for analysis, including 10 studies with pediatric population, two studies on adult patients (20,21), and one study (19) with a mixed pediatric and adult population ( Figure 1). Studies with adult patients were required to have an average age of 20 or greater; however, as this was a mean, these studies still likely reported some pediatric cases.…”
Section: Literature Searchmentioning
confidence: 99%
“…Manual search of reference lists did not yield any new studies. After applying the selection criteria, 13 comparative studies (6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) were finally included for analysis, including 10 studies with pediatric population, two studies on adult patients (20,21), and one study (19) with a mixed pediatric and adult population ( Figure 1). Studies with adult patients were required to have an average age of 20 or greater; however, as this was a mean, these studies still likely reported some pediatric cases.…”
Section: Literature Searchmentioning
confidence: 99%
“…The bias risk assessment showed that all studies had a low risk of bias [13][14][15][16][17][18][19][20][21] (Table 1). Studies have failed mainly on comparability between cases and controls and confirmation of the absence of the outcome at baseline.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…The use of different instruments to measure postoperative pain [13][14][15][16][17][18][19][20] and patient satisfaction 13,15,20 prevented these outcomes to be objectively evaluated. of the exposed of the exposed of the exposed of the exposed of the exposed the exposed the exposed the exposed the exposed the exposed Does not specify whether the outcomes are absent at the beginning of the study or if patients have previously been through the operative process.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…The age range of the patients who were qualified to the operation is wide in the literature, from 2 to 18 years (4,43). Adults are also operated (13,44).…”
Section: Discussionmentioning
confidence: 99%
“…The children with chest The results of the operation justify its wide application. The authors who compare Nuss and classic Ravitch procedure omit a very important aspect: a very exposed scar on the from wall of the chest versus two 2-3 cm scars in the axillary region (41,43) (fig. 5, 6).…”
Section: Discussionmentioning
confidence: 99%